Public Perception Toward Performance of Walikota Semarang Hendrar Prihadi, SE., MM. year period 2010-2015 - Hepy Riska Ilham; Budi Setiyono; Wachid Abdurahman (Journal of Politic and Government Studies, 2015)
Work quality is about doing the work and results of the work. Likewise with the government's work quality, success or failure the government to solve the existing problems in the region will influence the public perceptions of work quality of local governments, especially in the work quality of walikota. This research is analysed public perception toward work quality of Walikota Semarang Hendrar Prihadi year period 2010 – 2015. The method used in this research is quantitative. The research location in Semarang by taking five districts, namely Semarang Selatan, Semarang Tengah, Genuk, Gunungpati and Ngaliyan. The sampling technique in this research is propability Sampling Area. Teknic analysis used kuantitatif method for distribute answer in frequency from responden and described perception from research responden. The research results show that the public perception of government work quality of Semarang City led by Walikota Hendrar Prihadi has gone well, the aspect of public service, law, infrastructure development, and the environment already been good. Yet people still expect an increase in the development of public facilities more equitable, as well as the handling of floods that still occur in some areas of the City of Semarang. Suggestions in this research was the Walikota Semarang is expected to improve the quality of work through the achievement of targets and objectives to be achieved and is expected to pay more attention to the public and can accept criticism about the quality of the work to improve the social welfare on the City of Semarang.